Expressive Illocutionary Act Uttered by Main Characters in The Look Both Ways Movie - Ayu Novia Pratiwi; Komang Dian Puspita Candra (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research analyzes the types of expressive illocutionary acts in the Look Both Ways movie. Data were collected through non-participant observation by watching the film multiple times to identify and classify expressive utterances by the main characters, Nathalie and Cara. The data were categorized using Searle and Vanderveken’s (1985) theory, supported by Halliday and Hasan’s (1985) context of situation. A total of 39 expressive acts were found, with thanking (35.9%) as the most frequent. The context of situation field, tenor, and mode significantly influences the meaning and function of each act. This study highlights the importance of expressive illocutionary acts in building emotional connections and shaping character relationships, while also contributing pragmatic insights into film discourse and enriching linguistic research in cinematic contexts.